Effect of Analagesic Dose of Ketamine on Intraoperative Propofol Requirement and Postoperative Pain Relief After Diagnostic Gynaecological Laparoscopy - MUHAMMAD AHMAD KHAN, KHAWAJA RASHID HAFE, MOTSIM SHERAZ (Journal of Fatima Jinnah Medical University, 2018)
Background: Analgesic dose of ketamine given at induction reduces usage of propofol intraoperatively and requirement of opioid analgesic drugs postoperatively. Patients and Methods: Hundred patients were randomly allocated to two equal groups: saline or ketamine. It was a double blind study. Patients in both groups received premedication with midazolam and induction with propofol. Patients in ketamine group received 0.25 mg/kg ketamine at induction while the other group received saline. Anaesthesia was maintained with propofol infusion @ 6 mg/kg/min in both groups and additional boluses of propofol were used to deepen anaesthesia when required. Total amount of propofol used was noted at the end of procedure. Total amount of analgesic drug tramadol was also noted in the postoperative area at the time of discharge of patient. Results: Amount of propofol used in patients of ketamine group was significantly lesser than the saline group. There was no difference in the analgesic requirements in the postoperative ward. Conclusion: Ketamine in analgesic doses given at induction reduced the intraoperative propofol usage but had no effect on postoperative pain and analgesic requirement